2012
DOI: 10.1021/ma300459q
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Polyamides in the Presence of Water via Hydrophobic Hydration and Ionic Interactions

Abstract: In synthetic as well as natural polyamides, hydrogen bonding and conformations of amide motifs are strongly influenced by the presence of ions and their concentration, water molecules, and their structure, as well as the pH of the solution. This concept combined with solubility of synthetic aliphatic polyamides, in particular nylons, in water at elevated temperature and corresponding vapor pressure is evaluated as a new reversible shielding route in the processing of these polymers. So far, reversible shieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(67 citation statements)
references
References 33 publications
5
62
0
Order By: Relevance
“…Furthermore it was recently shown that formation of amide-amide hydrogen bonds can be hindered at high temperature by the strong solvation of amide groups by water molecules, inhibiting crystallisation and/or allowing dissolution of crystallites, as observed in waterimmersed Nylon-4,6 at a temperature of about 200 C [29][30][31]. The mobility of hydrogen bonds induced in the crystalline phase at high temperature by superheated water was also discussed in analogy with the Brill transition, which takes place in PA6 and consists in reorientations of hydrogen bonds within crystallites [32].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it was recently shown that formation of amide-amide hydrogen bonds can be hindered at high temperature by the strong solvation of amide groups by water molecules, inhibiting crystallisation and/or allowing dissolution of crystallites, as observed in waterimmersed Nylon-4,6 at a temperature of about 200 C [29][30][31]. The mobility of hydrogen bonds induced in the crystalline phase at high temperature by superheated water was also discussed in analogy with the Brill transition, which takes place in PA6 and consists in reorientations of hydrogen bonds within crystallites [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been proposed including preferential ionic hydration, water dipole orientation, electrostatic effects, osmotic effects and direct interaction between ions and macromolecules through van der Waals forces . A qualitative classification of ions considers two groups: kosmotropes, anions located to the left of chloride, are well hydrated anions proposed to increase the ordering of water molecules and tend to salt macromolecules out of solution and to stabilize folded conformations, and chaotropes, to the right of chloride, which are poorly hydrated, reduce the structuring of water and promote solubility and unfolding of macromolecules . Systematic studies of the role of specific ion effects in polymeric systems focused initially on aqueous PEO solutions and the influence on its phase behavior .…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] A qualitative classifi cation of ions considers two groups: kosmotropes, anions located to the left of chloride, are well hydrated anions proposed to increase the ordering of water molecules and tend to salt macromolecules out of solution and to stabilize folded conformations, and chaotropes, to the right of chloride, which are poorly hydrated, reduce the structuring of water and promote solubility and unfolding of macromolecules. [ 10 ] Systematic studies of the role of specifi c ion effects in polymeric systems focused initially on aqueous PEO solutions and the infl uence on its phase behavior. [ 8,11 ] More recently other polymeric systems have also been investigated such as poly(2-oxazoline)s, [ 12 ] poloxamers, [ 13 ] and polyamides.…”
Section: Introductionmentioning
confidence: 99%
“…16 While hydrolytic degradation was a concern in these processes, it was shown to be manageable for short residence times at 200 8C and may not pose a significant problem in melt processing methods such as extrusion or injection molding. 18 Finally, water has also been used to aid in montmorillonite dispersion for PA6 nanocomposites during extrusion. 19,20 While shH 2 O is known to dramatically affect the stability of PA crystal structures, its use as a processing aid for common commercial PAs has not been fully explored.…”
mentioning
confidence: 99%